Malaysia’s counter-terrorism strategy: a top-down policy analysis of legislative, rehabilitative, and educational approaches - Raja Mohd Naguib, Raja Muhammad Khairul Akhtar (IIUM Press, 2025)
This paper examines Malaysia’s implementation of the MyPCVE (Malaysian National Action Plan on Preventing and Countering Violent Extremism). It takes a top-down approach and focuses on the ability of policymakers to design clear and practical policy objectives and manage the implementation phase. Interviews were conducted with eight prominent figures and stakeholders who are involved in the implementation of this policy from various fields, including the MOHA (Ministry of Home Affairs), MinDef (the Ministry of Defence), the E8 or Counter-Terrorism Division of the RMP (Royal Malaysia Police), AIPA Caucus (Members of Malaysian Parliament and ASEAN Inter-Parliamentary Assembly Caucus), experts, and academics. The findings show that the plan is implemented centrally, with power passing from the first tier of government to the second tier and the third tier playing a less active role. The implementation consists of three phases: before, during, and after detention, with distinct stakeholders for each phase. These findings are helpful for law enforcement, intelligence agencies, and non-governmental organisations tasked with PCVE (Preventing and Countering Violent Extremism) in Malaysia.